Implikasi Poskolonialitas Relasi Kekuasaan Misi Katolik Dan Kolonial Belanda - Embu, Alfons No (Jurnal Masalah Pastoral, 2014)
There are various forms and dynamics of mission and power relationship in the early development of Christianity. By reading the history of Western colonialism of the East, will give clearly description that the mission was presented in conjunction with the colonial. In the Archipelago, the Catholic mission represented along the Portuguese colonization (1543-1666).2 Thus, VOC in 1606-1800 amputated this Catholic mission. And then, the mission reanimated in Nederland Hindia by King Louise Napoleon, the French Catholic of Dutch master in the 1800s. Nevertheless, power relationship of mission and the Dutch colonial government was in suffering situation. Dutch colonial government had a political interest in the presence of the Catholic mission. Conversely, the mission itself took advantages from its proximity of the Dutch colonialism. In fact, there was a kind of symbiotic mutualism between the mission and the Dutch colonial government. It brought the postcolonial impact to the life of Catholic mission during that time, and for the development of Indonesian local Catholic Church in future.